Just War Authority, Tradition, and Practice - Lang, Anthony F. 1968-; O'Driscoll, Cian; Williams, John 1969- (Washington Georgetown University Press, 2013)
The just war tradition is central to the practice of international relations, in questions of war, peace, and the conduct of war in the contemporary world, but surprisingly few scholars have questioned the authority of the tradition as a source of moral guidance for modern statecraft. Just War: Authority, Tradition, and Practice brings together many of the most important contemporary writers on just war to consider questions of authority surrounding the just war tradition. Authority is critical in two key senses. First, it is central to framing the ethical debate about the justice or injustice
16 The Wager Lost by Winning? On the ''Triumph'' of the Just War TraditionConclusion: Reclaiming the Just War Tradition for International Political Theory; Contributors; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based upon print version of record
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Transportation and state -- Congresses; Just war doctrine ; Congresses; Electronic books; Electronic books